(untitled) (Global Journal of Human-Social Science, 2015)
Recent deliverances by king Abdullah in Saudi Arabia (SA) has opened many doors for women over the past seven years. Women joined the consultative assembly in 2013, in the same year three women were named as deputy chair persons of three committees. In 2011 King Abdullah announced that women would be allowed to vote and run for office in the 2015 municipal elections. All these actions grant Saudi women the chance to occupy managerial positions in many organizations. However, Saudi women in managerial positions face many challenges. The purpose of this study is to recognize the challenges that female managers in public Saudi universities face in their managerial positions. The paper adopted an in-depth personal interviewsmethod in order to gain a deep understanding of the specific challenges faced by female managers in public universities. Nineteen female managers of which 10 were in high managerial positions of universities were interviewed. The study found that Saudi female managers face a number of challenges, the most important challenge is the long working hours, dealing with different natures of subordinates and lack of authorization. The study provided a number of recommendations to decision makers in order to alleviate those challenges such as the limitation of female long working hours by decentralization and better distribution of work load. Training programs in management and communication skills would help female managers to better manage and communicate with subordinates. Authorization should be given to female managers in order to be able to issue decisions necessary for their departments.